PERFORMANCE ANALYSIS OF WATER TREATMENT PLANT USING FAILURE MODE AND EFFECT ANALYSIS METHOD AND PREVENTIVE MAINTENANCE SCHEDULING: PERFORMANCE ANALYSIS OF WATER TREATMENT PLANT USING FAILURE MODE AND EFFECT ANALYSIS METHOD AND PREVENTIVE MAINTENANCE SCHEDULING - Febryanto, Indra Dwi (UNIPA PRESS, 2018)
The availability of pure water is a basic requirement of the Company,which is one of the main requirements for the production process in order for the Company to produce the cream.In order to meet the production needs ,the Company must have a Water Treatment Plant with good performance. A good Water Treatment Plant can produce a lot of pure water to meet the water requirements required by the Company. This research is needed to get a good Water Treatment Plant performance to improve the pure water of Company XYZ. This research uses FMEA (Failure Mode and Effects Analysis) method to classify which components require maintenance and scheduling . Scheduling in this research using RCM (Realibility Center Maintenance) method. In this research yield MTTRs and filter 0,48 hour,bag filter 0,68 hour, cartridge filter 1,22 hour.MTTF sanfilter 684 hours,bag filter 190.3hours,cartridge filter 236,8 hours.And MTBFs and filter with an average of 708 hours,bag filters with an average of 214.8 hours and a filter cartridge with an average of 260.8hours per year. In addition to MTTR, MTTF and MTBF other research is reliability (realibility) sand filter with value 0,178527412, bag filter with value 0,005394050, and cartridge filter with value 0,008884653.